Alterations and Associations Between Magnetic Susceptibility of the Basal Ganglia and Diffusion Properties in Alzheimer’s Disease - Liu, Xiuxiu; Du, Lei; Zhang, Bing; Zhao, Zifang; Gao, Wenwen; Liu, Bing; Liu, Jian; Chen, Yue; Wang, Yige; Yu, Hongwei; Ma, Guolin (Frontiers in Neuroscience, 2021)
This study adopted diffusion tensor imaging to detect alterations in the diffusion parameters of white matter fiber in Alzheimer's disease (AD) and used quantitative susceptibility mapping to detect changes in magnetic susceptibility. However, whether the changes of susceptibility values due to excessive iron in basal ganglia have correlations with the alterations of diffusion properties of white matter in patients with AD still unknown. We aim to investigate the correlations among magnetic susceptibility values of the basal ganglia, diffusion indexes of white matter, and cognitive function in patients with AD. 30 patients with AD and 19 healthy controls were recruited. Diffusion indexes of the whole brain were detected using tract-based spatial statistics. The caudate nucleus, putamen, and globus pallidus were selected as regions of interest and their magnetic susceptibility values were measured. Compared to healthy controls, patients with AD showed that there were significantly increased axial diffusivity (AxD) in the internal capsule, superior corona radiata, and right anterior corona radiata, increased radial diffusivity (RD) in right anterior limb of internal capsule, anterior corona radiata, and genu of corpus callosum, and decreased fractional anisotropy (FA) in right anterior corona radiata and genu of corpus callosum. The alterations of RD values, FA values, and susceptibility values of right caudate nucleus in patients with AD were correlated with cognitive scores. Besides, AxD values in right internal capsule, anterior corona radiata and superior corona radiata were positively correlated with the magnetic susceptibility values of right caudate nucleus in patients with AD. Our findings revealed that magnetic susceptibility of caudate nucleus may be an MRI-based biomarker of the cognitive dysfunction of AD and abnormal excessive iron distribution in basal ganglia had adverse effects on the diffusion properties of white matter.